Derivation and appraisal of maternal mortality estimates in Nigeria from the 2012 National HIV/AIDS and Reproductive Health Survey (2017)
Background Despite the huge burden of in Nigeria, accurate and reliable data fur maternal mortality measurement arc locking The federal Ministry of Health in collaboration with development partners included questions that allow indirect estimation of maternal mortality m us 2012 National HIV/AIDS and Reproductive Health Survey (NARHS) The aim of this paper was to derive estimates of Maternal Mortality Ratio (MMR) and Lifetime Risk of maternal death (LTR) from the 2012 NARHS data Methods: This was a secondary analysis of data from the maternal mortality module of NARHS 2012. During the survey, respondents (men aged 15-59 years and women aged 15-49 years) were selected via a multi-stage cluster sampling technique and data collected by trained field workers. In this study, report on survival or otherwise of adult female siblings were analysed to derive estimates of life tune risk of maternal death using the indirect sisterhood method. Results: Data from 15,596 men and 15,639 women were analysed A total of 12.810 adult female siblings had been exposed to the risk of death out of which 377 (2.9*4) have died of the 377 adult female deaths. 70 (18 6%) were pregnancy related the estimates of LTR and MMR were I in 71 women and 256 (95% CT. 196 - 316) maternal deaths per 100,000 live births respectively. There were north-south and rural-urban differences. Conclusion: The high level of maternal mortality is worrisome, concerted efforts aimed at reduction and provision of routine data for its measurement should be intensified.